Morbidity of juvenile onset inflammatory bowel disease: effects on education and employment in early adult life. Issue 5 (May 1994) - Ferguson, A; Sedgwick, D M; Drummond, J
Abstract : Seventy young adults (50 with Crohn's disease (CD) and 20 with ulcerative colitis (UC) (from a geographically derived cohort of patients with juvenile onset inflammatory bowel disease were interviewed and examined at a mean of 14 (range 5.2-29.5) years after diagnosis. Details of education and employment were collected as part of a structured clinical interview. Although 57% had had periods of absence from school of two months or more, their school examination pass rates were similar to those of the healthy population. The achievements of CD patients were consistently better than those of the UC group. In 15 patients, relapses of inflammatory bowel disease had adversely affected examination performance or prevented them from sitting school examinations. Extra tuition in hospital had been provided for only four patients, and three others had had privately arranged tuition at home. Fifty per cent proceeded to full time higher education. At the time of review, seven patients were full time students, one was a university research fellow, 47 were in full time and three in part time employment, one was self employed, four were housewives, and only six were involuntarily unemployed. All four unemployed CD patients attributed this to inflammatory bowel disease, but other factors were relevant in the unemployed UC patients. Few had direct evidence of rejection by employers on health grounds, though some did not declare their illness to prospective employers.